Digital Art History and the Museum: The Online Scholarly Collection Catalogues at the Art Institute of Chicago. (3rd April 2019) - Westerby, Genevieve; Keegan, Kelly
Abstract : This article considers the various ways that the Art Institute of Chicago's digital scholarly collection catalogues engage with art history in the digital realm. Since 2009, when the Art Institute of Chicago (AIC) was invited by the Getty Foundation to participate with a group of other museums to create a platform for museum collection catalogues online, the AIC has been a leader in this growing field. The digital platform we designed has proven to be the ideal vehicle to present our research in a dynamic manner. Through several case studies, we will demonstrate how these publications have not only made contributions to the field of digital art history through the presentation of primary archival source material online, but have also facilitated the incorporation of digital art history into our methodological toolbox. This paper also discusses the challenges of digital publishing as compared to more traditional, print-based workflows.